Effect of aging on the characteristics of meat from water buffalo grown in the Delta del Paraná region of Argentina - Irurueta, Martin; Cadoppi, Armando; Langman, Leandro Ezequiel; Grigioni, Gabriela Maria; Carduza, Fernando Jose (Elsevier, 2019)
Fifteen crossbreed water buffalos were selected from a farm in Delta del Parana´, Entre Rı´os Province, Argentina. Animals were castrated males 20–24 months old reaching final live weights of 400–420 kg. They were predominantly of Mediterranean and Murrah breeds and were feed in naturally grown pastures. Tenderness and chewiness increased with postmortem aging (p < 0.05). Aging did not affect flavour and odour scores, even though certain off-flavours and off-odours were reported. Changes in colour with aging were similar to those seen in beef